2019
DOI: 10.3389/fpls.2019.00610
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a GDP-Fucose Transporter and a Fucosyltransferase Involved in the Fucosylation of Glycoproteins in the Diatom Phaeodactylum tricornutum

Abstract: Although Phaeodactylum tricornutum is gaining importance in plant molecular farming for the production of high-value molecules such as monoclonal antibodies, little is currently known about key cell metabolism occurring in this diatom such as protein glycosylation. For example, incorporation of fucose residues in the glycans N -linked to protein in P. tricornutum is questionable. Indeed, such epitope has previously been found on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 95 publications
(155 reference statements)
0
21
2
Order By: Relevance
“…Chlamydomonas reinhardtii protein extracts were separated on a NUPAGE 4–12% gel electrophoresis and were electrotransferred onto nitrocellulose membrane as previously described (Zhang et al , ). Immunodetection with anti‐β(1,2)‐xylose‐specific antibodies (AS07 267; Agrisera, Vannas, Sweden) was performed according to Fitchette et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Chlamydomonas reinhardtii protein extracts were separated on a NUPAGE 4–12% gel electrophoresis and were electrotransferred onto nitrocellulose membrane as previously described (Zhang et al , ). Immunodetection with anti‐β(1,2)‐xylose‐specific antibodies (AS07 267; Agrisera, Vannas, Sweden) was performed according to Fitchette et al ().…”
Section: Methodsmentioning
confidence: 99%
“…B. braunii shows native N-glycans similar to human "hybrid" structures, and P. tricornutum presents paucimannosidic glycans, an important pattern found in a specific class of biopharmaceuticals (as explained in Section 5.1.2) [79,112]. Nonetheless, α(1,3)-fucose residues in P. tricornutum [113] and methylation of mannoses in B. braunii [110] are both N-glycan characteristics absent in humans.…”
Section: N-glycosylationmentioning
confidence: 96%
“…For examples, the heterologous expression of P. tricornutum GnTI restored the complex type N-glycans maturation in the Chinese hamster ovary (CHO) mutant, indicating its importance on the synthesis of complex type N-glycans ( Baïet et al, 2011 ). Subsequently, it was observed that the GDP-fucose transporter and FucT1 were involved in the fucose modification of proteins in P. tricornutum ( Zhang et al, 2019 ). In addition to P. tricornutum , the functions of genes, such as xylosyltransferase A (XylTA), xylosyltransferase B (XylTB), fucosyltransferase (FucT), and mannosidase 1A (Man1A) were studied during the protein N-glycosylation pathway of C. reinhardtii ( Mathieu-Rivet et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%